N2-methylguanosine and N2, N2-dimethylguanosine in cytosolic and mitochondrial tRNAs - Petrosyan, Jonny; Bohnsack, Katherine E. (Frontiers in RNA Research, 2024)
Decoration of cellular RNAs with modified RNA nucleosides is an important layer of gene expression regulation. Throughout the transcriptome, RNA modifications influence the folding, stability and function of RNAs as well as their interactions with RNA-binding proteins.Although first detected more than fifty years ago, the modified nucleosides N 2methylguanosine (m 2 G) and N 2,2 -dimethylguanosine (m 2 2G) have recently come to the fore through the identification and characterization of the human methyltransferases (MTases) responsible for their installation. In tRNAs, m 2 G and m 2 2G are present at the junctions between the acceptor stem and the D-arm, and the D-arm and the anticodon stem loop. Here, we review the current knowledge on the effects of mono-and di-methylation of N 2 of guanosine on base-pairing and provide an overview of m 2 (2)G sites in cytosolic and mitochondrial tRNAs.We highlight key features of m 2 G and m 2 2G MTases, and describe how these enzymes specifically recognize their RNA substrates and target nucleosides. We also discuss the impact of these modifications on tRNA functions, their dynamic regulation and their implications in disease.